Logging roads as surrogates for elephant trails: Facilitating social signaling by small forest ungulates despite increasing risks. Issue 7 (6th June 2019) - Naude, Vincent N.; Becker, François S.; Mayberry, Jillian L.; Vieira, Wilson F.; du Toit, Johan T.
Abstract: With global elephant populations in decline, a grave consideration is the loss of their ecological engineering effects that benefit other species, such as the maintenance of extensive trails through tropical forests. Anthropogenic roads can serve as surrogates for elephant trails despite exposing users to higher risk from bushmeat harvest. We explored the use of forest management roads by Weyns's duiker ( Cephalophus weynsi ) in Kibale Forest, Uganda. Faecal latrines were located on the road, clustered, and frequently revisited and replaced, with no latrines found in the surrounding forest or trails. Latrines occurred most frequently at road/trail intersections, at the road center, and where canopy and ground vegetation cover were lowest. Latrine decay in the forest was significantly higher than on the road and an exclusion treatment indicated coprophagous beetles as the primary agents of dung removal. Our findings demonstrate the dependence of a forest ungulate on roads for social signaling through dung, which is a behavior common to cryptic forest mammals that coevolved with trail‐forging megaherbivores. While logging roads pose multiple threats to forest biodiversity, the catastrophic decline of elephant populations means that forest managers must consider weighing these costs against the benefits of conserving at least some roads as surrogates for elephant trails. Abstract : Vincent Naude_Jillian Mayberry_Setting up exclusion cages in Kibale National Park.